Search for the doubly heavy [xi] 0bc baryon via decays to D0pK− - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2020)
A search for the doubly heavy Ξ0bc baryon using its decay to the D0pK- final state is performed using proton-proton collision data at a centre-of-mass energy of 13 TeV collected by the LHCb experiment between 2016 and 2018, corresponding to an integrated luminosity of 5.4 fb−1. No significant signal is found in the invariant mass range from 6.7 to 7.2 GeV/c2. Upper limits are set at 95% credibility level on the ratio of the Ξ0bc production cross-section times its branching fraction to D0pK− relative to that of the Λb0→D0pK− decay. The limits are set as a function of the Ξ0bc mass and lifetime hypotheses, in the rapidity range from 2.0 to 4.5 and in the transverse momentum region from 5 to 25 GeV/c. Upper limits range from 1.7 × 10−2 to 3.0 × 10−1 for the considered Ξ0bc mass and lifetime hypotheses.
Im Titel ist die Zahl "0" jeweils hochgestellt, "bc" tiefgestellt
Im Titel ist "-" hochgestellt
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, M. Dziewiecki, G. Frau, D. Gerick, J. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, A. Piucci, S. Stemmle, D.A. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und viele weitere]